Numinous Subjects Engendering the Sacred in Western Culture, An Essay - Tatman, Lucy (ANU Press, 2007)
Part religious studies, part feminist theory, part philosophy, part indescribable: such is Numinous Subjects. Described by the author as 'a kaleidoscopic exploration of why three gendered figures of the sacred matter within western culture,' the experience of reading this text truly is akin to gazing through a constantly turning kaleidoscope. Images, concepts, phrases and quotes are continually revisited, recombined, though never repeated in quite the same way. From these tumbling constellations arises a new understanding and wary appreciation of the figures of the virgin, the mother, and the whore. Drawing on the insights of thinkers as diverse as Rudolph Otto, Julia Kristeva, Simone de Beauvoir, and Martin Buber, Numinous Subjects simultaneously expands and focuses our attention on the myth of the sacred and its implications for female subjects in western culture today.